The Carbon Footprint Estimation based on Campus Activities in ITERA (Institut Teknologi Sumatera) - Kartika Sari, Novi; Gusvita, Rinda; Puradimaja, Deny Juanda (Universitas Diponegoro, 2021)
ITERA (Institut Teknologi Sumatera) is one of young university situated in Lampung Province, Indonesia. In 2018, the average population of campus (students, faculties, and staff) was about 9584 persons. The objective of this paper is to inventory Green House Gasses (GHGs) and then to calculate carbon footprint using equation by UI Greenmetric Guideline 2018 except for fuel and LPG consumption, paper use, and organic waste generation by using GHGs Protocol. Three scopes of GHGs emission were used to classify based on both direct and indirect source(s). The first scope was presented by LPG consumption and fuel consumption of campus’s car. Electricity consumption became scope 2 while the scope 3 involved paper use, organic waste generation including food waste and Yard trimmings, and transportation activities of both motorcycles and cars. The estimated GHGs emission was about 2846.541 metric ton CO2eq during 2018-2019 (one year) with the portion of each scope resulting 10.2%, 62%, and 28.2%, respectively. Electricity usage was being the highest contributor of carbon footprint. The inventory of GHGs will help top management of campus to evaluate and determine some strategies for minimization, reduction, and mitigation notably in electricity sector by some strategies such as substituting electric devices into eco-friendly products, applying energy management ISO 50001, and others.